IMPLEMENTATION OF FUZZY MEMBERSHIP FUNCTION TO DETERMINNE AUTOMATIC WATERINNG TIME - Novita Kurnia Ningrum; Ibnu Utomo Wahyu Mulyono; Karis Widyatmoko; Zahrotul Umami (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2023)
Global warming impacted to agriculture, thereby affecting the world's food supply. UNICEF calls on every country to be able to meet its food needs independently. Indonesia, as an agricultural country, has the potential to meet food needs independently. One effort that can be made is to combine existing agricultural systems with technology through the application of IoT. In this research, it was applied to citrus plants using DHT11 temperature and air humidity sensors and soil moisture sensor YL69. Data processing uses a fuzzy algorithm approach, using two input variables, namely temperature and humidity variables and soil moisture variables. Meanwhile, the resulting output variable is the time for watering the plants. At the fuzzification stage, each variable is grouped into three memberships. For temperature and humidity variables are divided into hot, medium and cold membership. Soil moisture variables are divided into wet, medium and dry membership. And the time variables consists of short, medium and long time membership. In the defuzzification stage, it is calculated by calculating the center of area value for each graphic area resulting from the fuzzification stage. Furthermore, to test the system, the testing carried out resulted in an error value of 5.19 percent. Based on test and trial that be done, the result shows that average volume of water that flows every second when watering plants is 36.5 ml per second.